2015
DOI: 10.3109/08830185.2015.1018418
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Testis Antigens and Immunotherapy in the Light of Cancer Complexity

Abstract: The ability of immunotherapy to evoke successful antitumor immune responses has been well documented over the past decade. Despite abundant preclinical data, it is only with the recent approval by the Food and Drug Administration (FDA) of the drugs such as sipuleucel-T and ipilimumab that immunotherapy is finally being recognized as a viable alternative to traditional therapies for treatment of various cancers. Despite the ability of immunotherapy to elicit successful antitumor immune responses, its efficacy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 81 publications
0
21
0
1
Order By: Relevance
“…Although lung cancer GWASs have identified dozens of lung cancer susceptibility loci, more lung cancer associated variants remained to be identified [3]. Cancer-testis genes were recognized as promising therapeutic targets for cancers due to their high immunogenicity in tumor tissues [22,23]. However, the roles of genetic variants in CT genes in the development of lung cancer have not been revealed in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although lung cancer GWASs have identified dozens of lung cancer susceptibility loci, more lung cancer associated variants remained to be identified [3]. Cancer-testis genes were recognized as promising therapeutic targets for cancers due to their high immunogenicity in tumor tissues [22,23]. However, the roles of genetic variants in CT genes in the development of lung cancer have not been revealed in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a number of cancer vaccine clinical trials are ongoing . Although some studies seem promising, a number of possible limitations in using CT antigens in targeted immunotherapy are yet to be overcome Merkel cell carcinoma (MCC) is a neuroendocrine tumor of the skin that behaves aggressively, with a 5‐year survival rate of only 18% in metastatic disease .…”
Section: Introductionmentioning
confidence: 99%
“…The expression of these antigens is normally restricted to the testis, but these antigens are also expressed (22)(23)(24). Several studies have revealed that CTAs are highly expressed in the tumor tissue of patients with HCC (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…SPAG9 belongs to the c-Jun-NH 2 terminal kinase-interacting protein family (28). Proteins from this family function in cell growth, proliferation, apoptosis and tumor development (29,30), and are expressed in renal cell carcinoma, and ovarian, cervical, breast, thyroid and colorectal cancer tissues, SPAG9 provokes a strong humoral immune response, and its autoantibody can be detected in the peripheral blood of patients with the aforementioned types of cancer (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The current study hypothesized that anti-SPAG9 antibody may be detected in the peripheral blood of patients with HCC, and that, in combination with serum AFP levels, it may provide a reliable diagnostic test for HCC, particularly for AFP-negative patients.…”
Section: Introductionmentioning
confidence: 99%